Participation In Decision-Making Among Trainers And Relationships With Job Satisfaction And Performance - Lunjew, Michael Dosim (1994)

(untitled)
This study was conducted to determine the nature of relationships between participation and job satisfaction and also with performance . It also sought to identify significant predictors , discriminant variables and valued outcomes from participation among trainers of public sector institutions in Malaysia . Finally,it attempted to determine whether or not Porter and Lawler's (1968) expectancy model could represent an appropriate framework for studying employee participation. A total of 250 trainers from the managerial and supervisory levels in eight public sector training institutions were studied.The study used structured questionnaires as the research instrument.